Serum osteoglycin level in relation to renal function and blood pressure in non-diabetic patients with hypertension - ZHAI Wenhui; HUANG Qifang; CHEN Yilin; LI Xiaodong; WANG Jiguang (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To investigate the association of serum osteoglycin (OGN) levels with renal function and blood pressure in non-diabetic patients with hypertension.Methods·Hypertensive patients without a diagnosis of diabetes mellitus were recruited from the Hypertension Department of Ruijin Hospital, Shanghai Jiaotong University School of Medicine. A total of 36 renal dysfunction patients (renal dysfunction group) and 38 normal renal function patients (normal renal function group), matched for age, gender and clinic blood pressure, were included in this study. Serum OGN concentrations were measured by the enzyme-linked immunosorbent assay (ELISA). Estimated glomerular filtration rate (eGFR) was calculated from serum creatinine using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation. The serum OGN levels were compared between the renal dysfunction group and the normal renal function group. The correlations of serum OGN level with eGFR and blood pressure were analyzed.Results·There was no significant statistical difference in serum OGN levels between the renal dysfunction group and the normal renal function group (P=0.708). Serum OGN levels were not significantly associated with eGFR (P=0.952). In the renal dysfunction group, mean arterial pressure, age and current smoking status were relevant factors of serum OGN levels (P<0.05). After adjustment for confounders, serum OGN levels were independently associated with clinic systolic and diastolic blood pressure, 24-hour ambulatory mean systolic and diastolic blood pressure in the renal dysfunction group (P<0.05), but not in the normal renal function group (P˃0.05).Conclusion·In non-diabetic patients with hypertension, serum OGN levels are not significantly associated with eGFR. In patients with renal dysfunction, higher serum OGN levels are independently associated with higher clinic systolic blood pressure, clinic diastolic blood pressure, 24-hour ambulatory mean systolic and diastolic blood pressure.